The Effect of Agarose on 3D Bioprinting - Chi Gong (MDPI AG, 2021)
In three-dimensional (3D) bioprinting, the accuracy, stability, and mechanical properties of the formed structure are very important to the overall composition and internal structure of the complex organ. In traditional 3D bioprinting, low-temperature gelatinization of gelatin is often used to construct complex tissues and organs. However, the hydrosol relies too much on the concentration of gelatin and has limited formation accuracy and stability. In this study, we take advantage of the physical crosslinking of agarose at 35–40 °C to replace the single pregelatinization effect of gelatin in 3D bioprinting, and printing composite gelatin/alginate/agarose hydrogels at two temperatures, i.e., 10 °C and 24 °C, respectively. After in-depth research, we find that the structures manufactured by the pregelatinization method of agarose are significantly more accurate, more stable, and harder than those pregelatined by gelatin. We believe that this research holds the potential to be widely used in the future organ manufacturing fields with high structural accuracy and stability.